Legal framework governing the carriage of liquified natural gas (LNG) within coastal water - Abdul Malik, Asmawi (2009)
The evitable of LNG evolution into coastal waters had reflected the lack and absent of clear guidelines on legal framework for governing the carriage of liquefied natural gas (LNG) within coastal water. IMO (Agenda item 21, MSC 83/INF.3/2007) did not pay direct attention to sustainable coastal water transport development. This is because the novelty of such industry and the traditional procedures of UN developmental bodies, normally needs sufficient time to consider a new and emerging phenomenon in their agenda of work. Thus it is a major source of inefficient and unsafe operation of the LNG carriage along the coast line. To date, there is no extension for LNG carriage within coastal water on every established rules and regulation. The main purpose of this study is to develop a legal framework model for the LNG transportation and carriage by using the IDEF0 structured modeling technique. The modeling process is divided into three phases, (i) the information gathering, (ii) the model development and (ii) the experts’ evaluation and validation. In the first phase, information on existing current legal practices were obtained through the literature study from applicable rules, regulations, conventions, procedures, policies, research papers and accident cases. In the second phase, a process model was drafted through an iterative process using the IDEF0 and the questionnaire is developed. From the questionnaire pilot test, each question blocks has shown an acceptable Cronbach’s Alpha value which is above 0.70. In the third phase, the preliminary of legal framework model is tested through forty five (45) potential respondents from various fields in legal practices and thirty eight (38) responded. A promising result was obtained where data exhibit normal distribution trend, even though every group has their own stand on the legal framework. The ANOVA output has generated P-values of 0.000. If P is less than or equal to the alevel, one or more mean value are significantly different. Through data correlation test, the correlated element blocks show a range of 0.0 to 0.4. A legal framework model for the LNG carriage within coastal water was constructed in the stand alone mode covering each aspect.